ANALISIS INTEGRASI PEMBIAYAAN SEKTOR PERTANIAN DAN NILAI TUKAR PETANI DI INDONESIA - Hafiiz Maulana (LPPM UNIMAL, 2018)
Islamic banking in the context of the agricultural sector has decreased performance in the proportion of financing. The existence of this alleged decline occurred because it was influenced by Farmer Exchange Rate. This study aims to identify the relationship between the financing performance of the Islamic banking sector and the Farmer Exchange Rate in Indonesia. The analysis used the Vector Error Correction (VECM) Model from January 2009 until December 2017. The results of the tests carried out consider the determinants of other variables in the form of non-performing financing and the based credit interest rate. Agricultural sector financing, in the long run, has a significant effect on increasing Farmer Exchange Rate, but this influence is not responsive in the short term. The findings predict that Non-performing financing will reduce the proportion of financing in the agricultural sector to Islamic banks. Determination of Basic Interest Rates Credit is the most responsive variable to changes in the financing of Islamic banking and Farmer Exchange Rates in Indonesia.